Analysis Solidarity of Jesus According to the Gospel of Mark and Its Relation to Christian Community Solidarity in Toraja - Darius, Darius; Saputra, Hardi; Teguh, Dimas (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2023)
Abstract: Â This study examines the concept of Jesus' solidarity as a reflection of the remarkable church in Toraja's Christian community's implementation of solidarity towards others. First, this study seeks to define the concept of Jesus' solidarity in Mark's Gospel. Second, describe the relationship between Jesus's solidarity in the Gospel of Mark and the Christian community's solidarity in Toraja. This study employs a qualitative descriptive approach in which the researcher describes the occurrences of Jesus' ministry-related solidarity in the Gospel of Mark. The researcher describes the texts in the Gospel of Mark, focusing on Jesus' solidarity theology. Text analysis on the theology of solidarity as a solid foundation for church solidarity must be implemented in church life, particularly for the Toraja Christian community. In addition to the approach or biblical analysis described previously, interviews were employed in this study. This interviewing procedure will be conducted to obtain information from informants regarding the church's solidarity efforts, particularly in Toraja. This comparative method reveals parallels between the solidarity of Jesus in the Gospel of Mark and church's solidarity in Toraja. The solidarity of Jesus is the foundation of church unity, which furthers the dissemination of the Gospel of Christ.Â Keywords: Solidarity, Jesus, Christian community, Toraja, Mark